The Abrahamic Stand at Nabī Yaqin: The Conversion Process of Holy Place - Amichay Schwartz (Religions, 2025)
The site of Nabi Yaqin preserves an ancient tradition of Abraham’s prayer over Sodom. The landscape that stretches from the ridge of Nabi Yaqin facing east to the Dead Sea and the Jordan River serves as the backdrop for the formation of this tradition. In this paper, we will show that the tradition regarding Abraham’s prayer apparently began during the Byzantine period as indicated by the writings of Egeria and St. Jerome. Although the exact location they identify cannot be determined from the sources, it seems that the region of Bani Na’im and Nabi Yaqin should be regarded as one space connected to the story of the destruction of Sodom. During the Middle Ages under Muslim rule Nabi Yaqin area became associated with Abraham’s prayer and a hollow in the ground at that location was marked as the place of his prayer. At a later stage, towards the end of the 17th century, two footprints were added to that socket. During the 18th and 19th centuries, an additional pair of footprints was added, which marked Lot’s prayer outside the compound. In Bani Na’im the neighboring village the burial place of the prophet Lot was identified. In fact, both sites are extensions of the story of the destruction of Sodom, with the former associated with its beginning and the latter with its end. We proposed that the process leading to these identifications was influenced by a site overlooking Lot’s Sea and Lot’s Cave, and the site itself became the burial place of Lot and the prayer site of Abraham.